2013
DOI: 10.1016/j.advwatres.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Fractional calculus in hydrologic modeling: A numerical perspective

Abstract: Fractional derivatives can be viewed either as handy extensions of classical calculus or, more deeply, as mathematical operators defined by natural phenomena. This follows the view that the diffusion equation is defined as the governing equation of a Brownian motion. In this paper, we emphasize that fractional derivatives come from the governing equations of stable Lévy motion, and that fractional integration is the corresponding inverse operator. Fractional integration, and its multi-dimensional extensions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(98 citation statements)
references
References 87 publications
0
97
0
1
Order By: Relevance
“…(4.3) reduces to 4) and interpreting the above equation, from the point of view of (2.8), (2.13) and (2.15), we have the required result. …”
Section: Fractional Differentiation Of Extended Generalized Mathieu Smentioning
confidence: 84%
“…(4.3) reduces to 4) and interpreting the above equation, from the point of view of (2.8), (2.13) and (2.15), we have the required result. …”
Section: Fractional Differentiation Of Extended Generalized Mathieu Smentioning
confidence: 84%
“…This was used to analyze the data collected by Klise [15]. The details of the conditioning have only recently appeared [4], but allowed us to rigorously test the sufficiency of the classical, Fickian advection dispersion equation [16]. In that paper, we challenged the notion that, based solely on a better fit to solute breakthrough data, a temporally non-local model is necessary for transport in an advection-dominated system.…”
Section: ) Multi-scale Variabilitymentioning
confidence: 99%
“…It has been demonstrated that the fractional order representation provides a more realistic behavior of complex systems appearing in various fields of science and engineering [3]. Due to this fact, fractional calculus has some applications in chemistry [4], bioengineering [5], hydrologic modelling [6], pharmacokinetics [7], heat transfer modelling [8], viscoelasticity [9], etc. In classical mechanics fractional calculus finds a wide range of applications, specially problems involving Lagrangian and Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%